High Efficiency Perovskite Solar Cells Exceeding 22% via a Photo‐Assisted Two‐Step Sequential Deposition. (9th December 2020) - Lee, Dong Geon; Kim, Dong Hoe; Lee, Jae Myeong; Kim, Byeong Jo; Kim, Jun Young; Shin, Seong Sik; Jung, Hyun Suk
Abstract: One of the most effective methods to achieve high‐performance perovskite solar cells (PSCs) is to employ additives as crystallization agents or to passivate defects. Tri‐iodide ion has been known as an efficient additive to improve the crystallinity, grain size, and morphology of perovskite films. However, the generation and control of this tri‐iodide ion are challenging. Herein, an efficient method to produce tri‐iodide ion in a precursor solution using a photoassisted process for application in PSCs is developed. Results suggest that the tri‐iodide ion can be synthesized rapidly when formamidinium iodide (FAI) dissolved isopropyl alcohol (IPA) solution is exposed to LED light. Specifically, the photoassisted FAI–IPA solution facilitates the formation of fine perovskite films with high crystallinity, large grain size, and low trap density, thereby improving the device performance up to 22%. This study demonstrates that the photoassisted process in FAI dissolved IPA solution can be an alternative strategy to fabricate highly efficient PSCs with significantly reduced processing times. Abstract : This work proposes an efficient method to produce tri‐iodide ions, which has been known as an efficient additive that improves the crystallinity, grain size, and morphology of perovskite films in a precursor solution using a photoassited process within short time, resulting in a device performance up to 22%.